Delivery of phenolics and caffeic acid phenethyl ester by propolis resin: Chewing gum system. (June 2021) - Bölük, Esra; Atik, Didem Sözeri; Kolaylı, Sevgi; Demirci, Ahmet Şükrü; Palabiyik, Ibrahim
Abstract: Chewing gums can act as a drug delivery system due to their long duration in the oral cavity. In this study, 26 sugary and sugar-free propolis added chewing gums were produced, and a D-optimal mixture design was used to optimize the amount of components based on the responses (texture, and sensory parameters). It was found that a high amount of propolis (10%) had a negative effect on sensory and textural properties of the samples, however, 5.06% and 4.75% propolis additions can improve the overall acceptance, taste, and odor of PSFC (sugar-free chewing gum) and PSC (sugary chewing gum), respectively. The biological activity of optimized PSC and PSFC were investigated in terms of total phenolic and flavanoid content, antioxidant power, and antibacterial effect against Streptococcus mutans . The results of the present study showed that the 5 min chewed PSC showed a higher inhibition zone on Streptococcus mutans, which was 7.10 mm. The second significant finding was that the total phenolic content, total flavonoid, and antioxidant power of the chewing gum bolus increased after the chewing simulation. Suitable bioactive molecule delivery kinetic model was used for the determination of caffeic acid phenethyl ester (CAPE) releasing, and CAPE was released 80% and 50% in 10 min for PSC and PSFC, respectively. One of the most significant findings in this study was that propolis resin was suitable for chewing gum formulations. Consequently, chewing gum can be a proper delivery product for transporting bioactive components of resin. Graphical abstract: Image 1